Information Diffusion in International Markets - Izquierdo, Alejandro (World Bank, Washington, DC, 2014)
Globalization has been a persistent phenomenon of the post-war period. The gross volume of cross-border capital flows has grown at an average of 25 percent a year, and trade in goods and services has also increased, albeit not as dramatically, but at least twice as fast as world GDP over the past 20 years. Yet, consumers and investors continue to spend and hold a disproportionate share of their assets in local markets-the so-called home-bias has been emphasized by many recent empirical studies. For many researchers, this home bias reflects information asymmetries and the fact that acquiring information across international borders is relatively costly. The main objective of the authors is to identify channels through which information gets disseminated across international markets. They consider three potential channels through which information can affect import and foreign equity purchase decisions in 14 OECD countries. The first channel consists of information spillovers from the commercial to the financial markets and vice-versa. Financial investors and importers share common information, which is also frequently conveyed to them by the same source-banks or financial intermediaries. The second and third channels emphasize seller and buyer reputations in international markets. The seller reputation channel stresses the importance given by, for example, importers in the United States who are considering buying products from Italy to the experience that Canadian and Japanese importers may have accumulated on Italian exporters. The buyer reputation channel examines to what extent a foreign investor or trader seeks information on the reliability of the foreign buyer by assessing his reputation in other countries. While the last two channels are equally important in explaining bilateral import flows, buyer reputation appears to be of greater importance for equity flows in the sample. The authors argue that these three channels may help provide some insights about the recent episodes of contagion across markets and countries that occurred over the past decade. These information channels can create virtuous or vicious circles that may, in turn, lead to unexpected changes in investors' and traders' behaviors across markets.